DETERMINANTS OF AGRICULTURAL CORPORATE CSR DISCLOSURE ON BEI - Veronika Enggarsih; Arif Nugroho Rachman (Berkala Akuntansi dan Keuangan Indonesia, 2021)
This study aims to determine the effect of profitability, leverage, and media exposure on CSR in agricultural companies listed on the IDX in 2015 - 2019. Sampling using purposive sampling technique as many as 15 companies with a span of time observations made for 5 years and selected as many as 75 objects of observation. The data analysis technique used multiple linear regression analysis with the help of the SPSS program. The results of this study indicate that profitability does not affect CSR disclosure, leverage does not affect CSR disclosure, while media exposure affects CSR disclosure.